42.4k views
5 votes
PLEASE SHOW YOUR WORK!!!

Solve for y: 3^3 + 14 y- (25y - 13) = y + 7y - 9y

User Terbubbs
by
5.8k points

1 Answer

2 votes


⟹

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

3^3+14*y-(25*y-13)-(y+7*y-9*y)=0

Equation at the end of step 1

((3³ + 14y) - (25y - 13)) - -y = 0

Pull out like factors :

40 - 10y = -10 • (y - 4)

Equation at the end of step3:

-10 • (y - 4) = 0

STEP4:

Equations which are never true:

Solve : -10 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation:

Solve : y-4 = 0

Add 4 to both sides of the equation :

y = 4


y = 4

User Rizwan Sharif
by
5.4k points